Analysis of the Implementation of Digital-Based Islamic Religious Education Learning in Improving Students’ Religious Literacy - Adib Riyadi; Moh. Ali (Research Horizon, 2026)
This study is driven by the need for educational digitalization, requiring innovation in Islamic religious education learning as a key factor in shaping students’ religious character. This study aims to analyze the implementation of digital-based Islamic religious education learning in improving students’ religious literacy. This study uses a qualitative approach with a case study method. Data collection techniques are carried out through interviews, observations, and documentation involving Islamic religious education teachers, students, and madrasahs. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the implementation of digital-based Islamic religious education learning is carried out through the use of learning media that are able to increase student involvement in the learning process. In addition, digital-based learning also contributes to improving students’ religious literacy, both in terms of understanding, attitudes, and religious practices. However, the implementation still faces several obstacles, such as limited infrastructure facilities and diverse levels of digital literacy among students. This study concludes that digital-based Islamic religious education learning has a significant role in improving students’ religious literacy if supported by the right learning strategies and adequate facilities.